Biofabrication: A Guide to Technology and Terminology. Issue 4 (April 2018) - Moroni, Lorenzo; Boland, Thomas; Burdick, Jason A.; De Maria, Carmelo; Derby, Brian; Forgacs, Gabor; Groll, Jürgen; Li, Qing; Malda, Jos; Mironov, Vladimir A.; Mota, Carlos; Nakamura, Makoto; et al.
Abstract : Biofabrication holds the potential to generate constructs that more closely recapitulate the complexity and heterogeneity of tissues and organs than do currently available regenerative medicine therapies. Such constructs can be applied for tissue regeneration or as in vitro 3D models. Biofabrication is maturing and growing, and scientists with different backgrounds are joining this field, underscoring the need for unity regarding the use of terminology. We therefore believe that there is a compelling need to clarify the relationship between the different concepts, technologies, and descriptions of biofabrication that are often used interchangeably or inconsistently in the current literature. Our objective is to provide a guide to the terminology for different technologies in the field which may serve as a reference for the biofabrication community. Trends: Biofabrication holds great potential in the fields of regenerative medicine and physiological 3D in vitro models by allowing the manufacture of complex tissue constructs with a higher degree of biomimicry to native tissues than do current biomedical solutions. As the number of biofabrication technologies being developed continues to expand, it is of paramount importance to adopt a concerted terminology framework and avoid generalizations. The ratio between the spatial resolution and the timescale of manufacture could be considered as a reliable measure to aid in the selection of an appropriate biofabrication technology for a desired application.